Pupillary light reflex in ethambutol-induced optic neuropathy - Yung-Ju Yoo (Nature Portfolio, 2020)
Abstract We evaluated changes in the pupillary light reflex (PLR) of ethambutol (EMB)-induced optic neuropathy and analyzed the correlations between PLR parameters and other structural changes in EMB-induced optic neuropathy. This retrospective, observational, case–control study involved thirty-two eyes of 17 patients with EMB-induced optic neuropathy (EON group), sixty eyes of 60 patients without EMB-induced optic neuropathy (non-EON group) while taking ethambutol, and forty-five eyes of 45 normal controls. PLR was measured by digital pupillometry. The clinical characteristics, optical coherence tomography measurements and PLR parameters including pupil diameter, constriction latency, constriction ratio/velocity, and dilation velocity were noted. The differences in PLR measurements were compared among the three groups. Correlations between PLR parameters and other structural parameters in EMB-induced optic neuropathy were evaluated. The pupillary constriction ratio, constriction and dilation velocities were significantly reduced in the EON group compared to the non-EON group and controls (all P < 0.05). In EMB-induced optic neuropathy, average outer macular ganglion cell layer (mGCL) thickness showed a significant correlation with the pupillary constriction ratio (ß = 4.14, P = 0.003) and maximal constriction velocity (ß = 1.08, P < 0.001). This study confirmed that pupillary constriction and dilation velocities were significantly decreased in patients with EMB-induced optic neuropathy, compared to normal controls. Digital pupillometry may be a useful tool in the evaluation of EMB-induced optic neuropathy.